Overcoming drug resistance of cancer cells by targeting the FGF1/FGFR1 axis with honokiol or FGF ligand trap - Szymczyk, Jakub; Sochacka, Martyna; Biadun, Martyna; Sluzalska, Katarzyna Dominika; Witkowska, Danuta; Zakrzewska, Malgorzata (Frontiers in Pharmacology, 2024)
Background: Chemoresistance of cancer cells, resulting from various mechanisms, is a significant obstacle to the effectiveness of modern cancer therapies. Targeting fibroblast growth factors (FGFs) and their receptors (FGFRs) is becoming crucial, as their high activity significantly contributes to cancer development and progression by driving cell proliferation and activating signaling pathways that enhance drug resistance.Methods: We investigated the potential of honokiol and FGF ligand trap in blocking the FGF1/FGFR1 axis to counteract drug resistance. Using PEAQ-ITC, we verified direct interaction of honokiol with the FGFR1 kinase domain. We then demonstrated the effect of FGF1/FGFR1 inhibition on taltobulin resistance in cells expressing FGFR1. Finally, we generated drug-resistant clones by prolonged exposure of cells with negligible FGFR levels to taltobulin alone, taltobulin and honokiol, or taltobulin and FGF ligand trap.We demonstrated for the first time a direct interaction of honokiol with the FGFR1 kinase domain, resulting in inhibition of downstream signaling pathways. We revealed that both honokiol and FGF ligand trap prevent FGF1-dependent protection against taltobulin in cancer cells expressing FGFR1. In addition, we showed that cells obtained by long-term exposure to taltobulin are resistant to both taltobulin and other microtubule-targeting drugs, and exhibit elevated levels of FGFR1 and cyclin D. We also found that the presence of FGF-ligand trap prevents the development of long-term resistance to taltobulin.Our results shed light on how blocking the FGF1/FGFR1 axis by honokiol and FGF ligand trap could help develop more effective cancer therapies, potentially preventing the emergence of drug-resistant relapses.